Recrystallization and martensitic transformation in nanometric grain size Cu-Al-Ni thin films grown by DC sputtering at room temperature - Morán; M. J.; Condó; A. M.; Haberkorn; N.; Haberkorn, Néstor (Elsevier, 2018)
Fil: Morán; M. J. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina; Universidad Nacional de Cuyo; Argentina